Análise sistêmica dos fornos de cozimento de anodo para a indústria de alumínio - Tiba, Paulo Roberto Teruo (2010)
The recent global economic crisis allied with the trend for sustainable companies and countries have meaningfully changed the aluminum area. Previously, the productivity was the main focus of the metal producer and no concern regarding the impact of this activity in the environment was considered. Nowadays, the search for low metal production cost, the reduction of residues and energy-saving aspects are the driving-force for the companies’ competitiveness increase. In this sense, the materials research can be an additional tool as providing new technologies and improvements to the metal production process. Therefore, a systemic analysis was performed for anode baking furnaces considering the dense refractory materials, the post mortem analysis, the insulating materials and the heat transfer. The results attained for the mechanical and thermomechanical characterization of the dense refractories led to insights for the furnace maintenance cost reduction, such as the choice of high performance compositions and the frequent chemical control of both, fluid coke and green anode. Additionally, this work allowed better commercial inputs for the aluminum producer due to the technical development of new refractory suppliers. Regarding the insulating materials and the heat flow, alternatives for energy-saving were visualized, highlighting the use of an insulating blanket on the upper part of the furnace. As a conclusion of this work, the correlation between refractory, energy, sustainability and productivity was better understood for anode baking furnaces, besides the development of novel actions for the aluminum company in order to improve its competitiveness.